DEKONTRUKSI KONSEP NUSYUZ DALAM HUKUM KELUARGA ISLAM DAN FAQIHUDIN ABDUL KODIR: Dekonstruksi Nusyuz menuurut Faqihudin Abdul Kodir, Dekonstruksi Nussyuz menurut Kompilai Hukum Islam, Analisis Studi Perbandingan Dekonstruksi Nusyuz menurut Faqihudin Abdul Kodir dan Kompilasi Hukum Islam - Ani Nuraeni; Didi Sukardi; Abdul Aziz; Ahmad Khalimy (Jurnal Studi Islam, 2025)
The assumption that the concept of nusyuz in Islamic law tends to be patriarchal bias so that there needs to be a deconstruction of the meaning in a gender-fair manner. So the purpose of this study departs from Faqihuddin Abdul Qodir's review which raises. The issue of mutuality to analyze the concept of nusyuz, its similarities and comparisons between Faqihuddin Abdul Qodir's perspective and the Compilation of Islamic Law fairly and in depth. This study uses a descriptive-qualitative method accompanied by a literature study (library research). The results of this study can be summarized as first, in the Compilation of Islamic Law, nusyuz can be defined as an attitude when a wife does not want to carry out her obligations, namely: the main obligation to be devoted physically and mentally to her husband and other obligations are to organize and manage daily household needs as well as possible. Second, the perspective of Faqihuddin Abdul Kodir, a figure who initiated the theory of mubadalah (mutuality) between men and women, stated that from the perspective of mubadalah, nusyuz is the opposite of obedience which is negatively oriented towards relationships. It is done by either husband or wife. Third, the analysis of the meaning of nusyuz can be reviewed from the KHI and the perspective of Faqihuddin Abdul Kodir to be more comprehensive. There is a difference in the meaning of nusyuz between the Compilation of Islamic Law and Faqihuddin Abdul Kodir which lies in the allocation and standard of fulfillment of family responsibilities. The similarities are found in the source of interpretation and the purpose of marital balance. In this analysis, the presence of Faqihuddin Abdul Qodir's concept of mutuality can be used as a reference in building the enforcement of nusyuz in Family Law that is more gender-equitable today. Keywords: Nusyuz, Deconstruction, Compilation of Islamic Law, Faqihuddin Abdul Kodir